PENGARUH SOSIAL MEDIA DALAM MEMBENTUK PERSEPSI PEMUDA TERHADAP PARTISIPASI POLITIK - Grace Anika Susilowati (Ikon --Jurnal Ilmiah Ilmu Komunikasi, 2021)
In 1998, all the information controlled by government. In the past, people not allowed to speak their aspiration or opinion about government decision. But now, we are entering communication freedom. People can speak up about their aspiration and opinion in public. People can influence government decision. There are no limit to speak up now. Our communication freedom also regulated in The 1945 Regulation of Republic of Indonesia Article 28F stated that we have rights to get information, to share information and to keep information. Now a days, we are as Indonesia people too free to speak up. No limitless to share our aspiration. Social media has no gate keeper which mean that no one can control the information. It cause hoax or fake information, provocative campaign and hostility. The writer conduct this research using quantitative methodology. The purpose of this research are to find, investigate and to analyze the effectiveness to use Instagram as communication platform to shape youth perception. Data from Kontan Magezine stated that more than 40% voters dominated by youth. This is a big opportunity and big challenge for politicians to win the election. Politicians compete to win youth heart. It is not easy to steal youth attentions. How politicians build relationship with youth? How politicians get engage with youth? The new strategy campaign is using social media to build relationship. They are post every activity to impress youth. They are make program or campaign program and ask youth to join and support the program. The purpose of using social media is to shape youth perception. Another issue is youth is lack of interest to get involve in politic activity. They are skeptic for every political activity. The stigma is political participation is about giving your vote in the election. But in this research, writer find out that voting is not only political participation. Talking about politic with friends, follow or commenting on candidate’s instagram account are include political participation. This research using media ecology studies, perception theory and political participation theory. Questionnaire is the instrument of this research to collect data. Banteng Muda Community as the respondent. Banteng Muda Community is youth community under Indonesian Democratic Party of Struggle. They used to be success team to support Mr. Joko Widodo and Mr.Jusuf Kalla to win presidential election in 2014. Now, Banteng Muda Community concern in social issue around Indonesia. The finding of this research are Instagram is an effective communication platform to transfer message and information. Instagram success to shape youth perception and influence youth to take action in political participation.